Having a bad attitude? The relationship between attitudes and sickness absence - Karen Evelyn Hauge; Marte Eline Ulvestad (IZA Journal of Labor Policy, 2017)
Is sickness absence related to attitudes? Several studies point to attitudes as an important factor for sickness absence. We study the relation between sickness absence and attitudes towards possible reasons for sick leave, towards cheating and towards work, by linking a survey among Norwegian healthcare workers, aimed at identifying attitudes, to detailed data on sickness absence from the employers. We find that there is an association between sickness absence and certain attitudes but mainly for self-certified sick leave. Employees with more lenient attitudes towards sick leave have more self-certified sick leave, but not more GP-certified sick leave. Furthermore, we find no evidence of attitudes being able to explain the persistently observed differences is absenteeism between different demographic groups.
Keywords: I1; I12; J01; J45; 330; Norway; Sickness absence; Attitudes; Absenteeism; Demographic groups; Gender; Survey; Healthcare sector